ThIAS (Thief Indication Alarm System) Security Device of Livestock in Animal Cages Based on Light Dependent Resistor (LDR) and Microcontroller Arduino - Rahmadi, Aji; Dimisa, Adi Ahmad; Kurniawan, Asep; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2019)
Research on Thias (Thief Alarm Indication System) safety device of livestock in animal cages based on the Light Dependent Resistor (LDR) and the Arduino microcontroller has been done. This research aims to design and characterize an alarm system or test the success rate of the alarm system. This study can be used as an alarm when livestock theft is occurring. The method used in this research is divided into three stages, design, manufacture and testing. The working principle of this alarm system, when the laser beams hitch the LDR, then the high value of the resulting LDR then produces an alarm notification in the form of sound. The hitch here is a thief entering or exiting the cage. To control the performance of the alarm system use the Arduino microcontroller. Obtained results from this research is a prototype alarm system. From testing, this alarm system obtained a success rate of 100%. The advantages of this alarm system are cheap and simple.